Valor diagnóstico de citología cérvicovaginal e histología de cérvix en la determinación del cáncer de cuello uterino - Guamán Ñamo, Evelyn Katherin (2022)
Abstract Worldwide, the fourth leading cause of death is cervical cancer. Several methods and techniques exist for its identification: conventional cytology, liquid-based cytology, biopsy and histology and confirmatory immunohistochemically tests. This work aimed to gather information on the diagnostic value of cervicovaginal cytology and cervical histology in the determination of cervical cancer. This research was based on a descriptive, non-experimental, bibliographic documentary design. The population studied was formed from 89 bibliographic sources, which were filtered by considering the inclusion and exclusion criteria, obtaining a sample from 63 documents of Scielo, PudMed, Elsevier, Recimundo, Google Scholar, Medigraphic, Springer, and Official Pages. With the analysis and discussion of the different authors, the results obtained from this research were: that liquid-based cytology is the best option for most researchers; however, the conventional technique is still advantageous when resources are scarce. For the report, it is essential to use the Bethesda System for its y advantages and constant updating. In addition, the histology and immunohistochemistry tests are the substantial part to confirm in a diagnosis whether or not there are intraepithelial lesions of high grade HSIL, low grade LSIL, and invasive carcinoma. Keywords: Cervical cancer, Conventional Cytology, Liquid Cytology, Histology, Immunohistochemistry, cervix.